2008
DOI: 10.3354/ab00094
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of enzyme activities linked to acid–base regulation in a deep-sea and a sublittoral decapod crab species

Abstract: When compared to the sublittoral Dungeness crab Cancer magister, the deep-sea Tanner crab Chionoecetes tanneri exhibited lower activities of enzymes involved in some of the processes essential for efficient acid -base regulation. Tissue enzymatic activities were compared between Dungeness crabs held in normoxia and Tanner crabs held in hypoxia -both treatments mimicking typical habitat oxygen levels. In the posterior gill, activities of all forms of ATPase and carbonic anhydrase (CA) were approximately 2-to 13… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 45 publications
1
3
0
Order By: Relevance
“…Increasing the concentration of the Na + /K + -ATPase-specific inhibitor ouabain did not alter the results, suggesting that other ATPases may be highly active in the gills of P. borealis. The results of the present study and the findings of Pane et al (2008) may indicate that when exposed to environmental hyper capnia, decapod crustaceans can maintain pH e without increasing the activity of ion-transporting enzy mes above the basal metabolic level. However, the activity of other enzymes in volved in acid -base regulation, such as carbonic anhydrase, could be altered to increase acid -base regulation during hypercapnic exposure (Burnett et al 1981, Henry & Cameron 1983.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Increasing the concentration of the Na + /K + -ATPase-specific inhibitor ouabain did not alter the results, suggesting that other ATPases may be highly active in the gills of P. borealis. The results of the present study and the findings of Pane et al (2008) may indicate that when exposed to environmental hyper capnia, decapod crustaceans can maintain pH e without increasing the activity of ion-transporting enzy mes above the basal metabolic level. However, the activity of other enzymes in volved in acid -base regulation, such as carbonic anhydrase, could be altered to increase acid -base regulation during hypercapnic exposure (Burnett et al 1981, Henry & Cameron 1983.…”
Section: Discussionsupporting
confidence: 67%
“…However, the effect of hypercapnic exposure on gill Na + /K + -ATPase activity in decapods has been poorly investigated. Pane et al (2008) found significantly decreased Na + /K + -ATPase activity in Dungeness crabs Cancer magister exposed to pCO 2 of 10 000 µatm for 24 h, and no change was found in the deep-sea crab Chionoecetes tanneri subjected to the same conditions. Using both microarray and quantitative PCR, Fehsenfeld et al 2011found only small changes in gene expression of proteins known to be important in osmoregulation and acid -base regulation, while other membrane proteins were differentially regulated in response to elevated seawater pCO 2 (3900 µatm) under low salinity conditions.…”
Section: Discussionmentioning
confidence: 77%
“…However, the efficiency of crustacean buffering varies among species depending on their natural environment (Pane et al, 2008;Whiteley, 2011) and within life-history stages (Bouaricha et al, 1991). Thus, it is probable that early developmental stages of intertidal crustaceans vary in sensitivity to high CO 2 as a consequence of physiological adaptations to their respective environments, with larval stages expected to be most vulnerable to future ocean acidification.…”
Section: Introductionmentioning
confidence: 99%
“…Each CT (7.6-liter RubberMaid Model 1530 water cooler) is equipped with a float valve to regulate seawater input, sensors (T, DO, pH), a gas input line connected to a diffuser stone, a 600-watt heater, and a drain with a distribution manifold that connects delivery rates according to pH and DO set points. The GCA has supported several studies evaluating the response of a variety of deep-sea animals to future deep-sea conditions (e.g., Pane and Barry, 2007;Pane et al, 2008;Kim et al, 2013a,b;Taylor et al, 2014;Hamilton et al, 2017).…”
Section: Seawater Control Systemmentioning
confidence: 94%